Factors Influencing Halal Cosmetics Decision Making in Bandung, Indonesia - Astuti Pratminingsih, Sri (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted to understand the buying behavior of halal cosmetics and the factors that influence consumers to buy halal cosmetics. The study relies on the Theory of Planned Behavior model, which consists of attitude, subjective norms, and perceived behavioral control. The sample in this study consists of 200 female respondents who consume halal cosmetics. Data collection is done by using a five-point Likert scale questionnaire, which is then analyzed using regression analysis techniques. Results of this study found that three antecedents of intention, namely attitudes, subjective norms, and perceptions of behavioral control, have a positive influence on consumer buying decisions to buy halal cosmetics.